Reviewing the Impact of COVID-19 on the Performance of Small Industries in South Sumatra - Mukhlis Mukhlis; Bernadette Robiani; Nazeli Adnan; Hamira Hamira; Dirta Pratama Atiyatna (Jurnal Ekonomi Pembangunan, 2022)
In early 2020, the COVID-19 virus outbreak spread globally and had a negative impact on the economy. The large-scale social restriction policy implemented by the South Sumatra government to contain the development of the virus has had a negative impact on small industries. This study aims to analyze the impact of COVID-19 on small industries in South Sumatra Province. The data used are primary data from 60 samples of small industries and secondary data sourced from agencies. The analysis technique used is quantitative and qualitative analysis techniques. The results of the Wilcoxon signed test show that the COVID-19 pandemic has caused a decline in profits and labor in small industries in South Sumatra Province. Small industries have felt the negative impact of the presence of COVID-19 but they can still survive and it is easy for their businesses to get back on their feet. For this reason, various policies are needed to develop small industries in South Sumatra Province.